THE EFFECT OF TAX AVOIDANCE, EARNINGS MANAGEMENT AND POLITICAL CONNECTION ON CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE : INDONESIAN MANUFACTURING COMPANIES EVIDENCE - Mala Ayu Anggita; Trisandi Eka Putri; Asep Kurniawan (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2019)
The purpose of this study to determine the effect of tax avoidance, earnings management, and political connection on the corporate social responsibility disclosure (case studies on manufacturing companies listed on the idx for the period 2016-2017). This study uses a quantitative approach. The population in this study were all manufacturing companies listed on the IDX for the period 2016-2017. The analytical method used in this study is descriptive analysis, classic assumption test and multiple linear regression analysis. The results showed that partially, tax avoidance and earnings management had no effect on corporate social responsibility disclosure, and political connections had a positive effect on corporate social responsibility disclosure. While simultaneously, tax avoidance, earnings management and political connection have an effect on jointly on corporate social responsibility disclosure